1999
DOI: 10.1021/jm990009f
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial Approach to the Identification of Dipeptide Aldehyde Inhibitors of β-Amyloid Production

Abstract: In an effort to rapidly identify potent inhibitors of Abeta production and to probe the amino acid sequence specificity of the protease(s) responsible for the production of this peptide, a large number of dipeptide aldehydes were combinatorially synthesized and manually evaluated for their inhibitory properties. The starting point for this study was the dipeptide aldehyde carbobenzoxyl-valinyl-phenylalanal previously shown to inhibit the production of Abeta in CHO cells stably transfected with the cDNA encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…1B). The selective inhibition of cleavages other than A␤ 42 by GVV is qualitatively similar to the effects on A␤ production observed with pepstatin (11), other peptide aldehydes (23), and some difluoroketone compounds (21); however, GVV appears to be even more selective than those previously reported with doses that inhibit A␤ 40 by Ͼ90% while not inhibiting A␤ 42 production. Significantly, we have recently observed selective inhibition of A␤ 40 production by GVV, pepstatin, and other peptide aldehyde inhibitors in an in vitro assay of ␥-secretase activity, 2 indicating that the selectivity is not simply an issue of differential cell penetrance of the inhibitor.…”
Section: ␥-40 and ␥-42 Secretase Activities Are Pharmacologically Andsupporting
confidence: 79%
“…1B). The selective inhibition of cleavages other than A␤ 42 by GVV is qualitatively similar to the effects on A␤ production observed with pepstatin (11), other peptide aldehydes (23), and some difluoroketone compounds (21); however, GVV appears to be even more selective than those previously reported with doses that inhibit A␤ 40 by Ͼ90% while not inhibiting A␤ 42 production. Significantly, we have recently observed selective inhibition of A␤ 40 production by GVV, pepstatin, and other peptide aldehyde inhibitors in an in vitro assay of ␥-secretase activity, 2 indicating that the selectivity is not simply an issue of differential cell penetrance of the inhibitor.…”
Section: ␥-40 and ␥-42 Secretase Activities Are Pharmacologically Andsupporting
confidence: 79%
“…This "A␤ rise" phenomenon, the same inhibitor causing an increase in A␤ at low concentrations but inhibition at higher concentrations, has been observed frequently (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). For peptide aldehyde inhibitors, some studies reported a rise that was specific for A␤42 (3)(4)(5)(6), whereas other studies reported a rise also for A␤40 in addition to A␤42 (7)(8)(9)(10). However, these studies also differed as to the pharmacological target proposed to mediate the effects on A␤; some authors considered only the protease calpain via an indirect effect on ␥-secretase (7,9,10), whereas others proposed a direct effect on ␥-secretase (3)(4)(5)(6)8).…”
mentioning
confidence: 72%
“…For peptide aldehyde inhibitors, some studies reported a rise that was specific for A␤42 (3)(4)(5)(6), whereas other studies reported a rise also for A␤40 in addition to A␤42 (7)(8)(9)(10). However, these studies also differed as to the pharmacological target proposed to mediate the effects on A␤; some authors considered only the protease calpain via an indirect effect on ␥-secretase (7,9,10), whereas others proposed a direct effect on ␥-secretase (3)(4)(5)(6)8). In one study, the A␤ rise was reported in isolated membrane preparations, suggesting a direct effect of peptide aldehydes on ␥-secretase (6).…”
mentioning
confidence: 99%
“…Determination of A␤ Levels by Enzyme-linked Immunosorbent Assay-The ability of compounds to lower A␤ secretion was tested using Chinese hamster ovary cells overexpressing wild-type ␤ APP as described previously (20) and Roach et al 2 Briefly, confluent cells were incubated with a range of concentrations of compounds for 16 h in serum-free medium containing 0.2% bovine serum albumin. A␤ 1-40 in the resultant conditioned media was quantified by sandwich enzymelinked immunosorbent assay using a position 40 neoepitope-specific monoclonal antibody and a biotinylated monoclonal antibody directed to A␤ residues 10 -20.…”
Section: Methodsmentioning
confidence: 99%